A Rarely Seen Fetal Anomaly: Fraser Syndrome - Tosun, Miğraci; Ulusoy, Özlem; Kökcü, Arif; Çetinkaya, Mehmet; Aydın, Oğuz; Oğur, Gönül (Gynecology Obstetrics & Reproductive Medicine, 2009)
There are about 200 published case reports of patients with Fraser syndrome and several comprehensive reviews have previously been published. Fraser syndrome has a recurrence risk of 25% among siblings, therefore prenatal diagnosis is an important task for the diagnostician counseling affected families. We aimed to report a case of Fraser Syndrome that was diagnosed prenatally at 19 weeks of gestation with multiple ultrasonographic anomalies and terminated at 21 weeks of gestation, to review prenatal diagnostic criteria and possible etiologic factors of Fraser syndrome.